Morocco : Cost Assessment of Environmental Degradation - World Bank (Washington, DC, 2013)
This report is the first step in a process toward using environmental damage cost assessments for priority setting and as an instrument for integrating environmental issues into economic and social development. The report provides estimates of damage cost for several areas of the environment: air, water, land and forests, and waste disposal. The estimates should be considered as orders of magnitude and a range is provided to indicate the level of uncertainty. As areas of priority are identified, further analysis will be required for more accurate estimates. Due to data limitations, the damage cost of environmental degradation has not been estimated in several areas: industrial, hazardous, and hospital waste disposal; unsanitary landfills; degradation of natural ecosystems and biodiversity; and groundwater resource degradation and over-extraction. In addition and due to the complexity of the problem, the report only partially captures damage resulting from soil degradation. The report points t the need to further assess and quantify current and potential future damage costs related to those impacts.